Mode-locked fiber laser with a manganese-doped cadmium selenide saturable absorber - Rosol, Ahmad Haziq Aiman; Rahman, Husna Abdul; Ismail, Ezzatul Irradah; Jusoh, Zulzilawati; Latiff, Anas Abdul; Harun, Sulaiman Wadi (Optical Society of America, 2017)
We demonstrate the generation of mode-locked pulses in an erbium-doped fiber laser (EDFL) by using a new manganese-doped cadmium selenide quantum-dots-based saturable absorber. The laser produces a soliton pulse train operating at 1561.1 nm with a repetition rate of 1 MHz, as the pump power is varied from 113 to 250 mW. At the maximum pump power, we obtain the pulse duration of 459 ns with a signal-to-noise ratio of 50 dB.